Estudio comparativo de técnicas digitales de reducción de ruido para su posible uso en auxiliares auditivos - Solís Estrella, H.; Gutiérrez Aldana, A. (Revista Mexicana de Ingenieria Biomedica, 2006)
In this paper we present a comparative study of four signal processing techniques focused to solve the environmental noise problem in hearing aids, aiming to restore speech communication to the maximum possible degree. The evaluated techniques are the RACE adaptive filter, the Spectral Subtraction, the Singular Value Decomposition based noise reduction and the Independent Component Analysis. The techniques were evaluated by computing the improvement to the signal-to-noise ratio in different environments and performing statistical significance tests on the results. The Independent Component Analysis obtained the best results, which in a simulation environment is able to restore the speech signal even when its energy level is 15dB under that of the noise.